URGENSI HUKUMAN BERAT BAGI PELAKU TINDAK PIDANA KORUPSI - Petrus Irwan Pandjaitan (to-ra, 2015)
AbstractFinancial Loss of State is the basis to declare the existence of Corruption Crime Action, and thebasis to punish the doers is UURI No 31 year 1999 subject Fighting of Corruption to classify theforms of the punishment, such as : dead sentence, inprison, fines, substation money and take over ofaset, in criminal law it is confessed a logic which states that dangerous nature and damage of anaction become the reason to criminalize an action as a criminal action, and have to have falses,because just only by having falses a person can be punished, but it has to have coorelation betweenthe action that cause loss with the punishment given, in the form of the state financial in certainamount, corruption as an extra ordinary crime, conducted by many official Officers and the countryexecutors, besides, corruption has damage Behavior and mental of the executors which areaccustomed to live with luxiouristy, the corrutption itself has cause loss for public and the doersshall be given fair punishment that is the punishment as heavy as possible or dead sentence ifnecessary, to punish the doers of corruption, shall have certain purpose, such as to save stateproperty, to stop the doers of doing such things, and to prevent other people not to conbductcorruption, by that way it is necessary to punish the doers of corruption with heavy punishmentsimply not only to stop of doing corruption but it is understood as a form of justice and recovery ofsocial relation between the Doer and the state and the public, so that later on after the doer hascompleted its punishment it will not rejected by the public.Kata Kunci : Hukuman berat